Implementation Of Watermarking Using The Singular Value Decomposition Method - Satria Yudha Prayogi; Sony Bahagia Sinaga (Sean Institute, 2021)
Technological developments have made it easy for the distribution of digital data (such as text, images, audio, and video) both with disk media and through internet media. On the other hand, this convenience can cause problems with copyright protection. One technique to overcome this problem is to insert a sign (watermark) as proof of ownership into digital data known as watermarking. Watermarks can be inserted into the spatial domain or the frequency domain. In general, watermarking in the frequency domain is more resistant to attacks than watermarking in the spatial domain. The watermarking method used in this study uses a transformation domain, namely Singular Value Decomposition (SVD). Tests used to provide a blurring effect). Where the technique using Singular Value Decomposition (SVD) is generally inserted into singular values based on the consideration that the singular value will not experience significant changes if there is a slight disturbance in the image.